A descriptive survey skin color perception of kayumanggi Filipina in color choices of clothing - Ang, Unica Cordovilla (College of Home Economics, University of the Philippines, 2009)
This research serves as a pilot study on how skincolor perception of kayumanggi Filipina is reflected on her color choice sin clothing. The general objective of this study was to investigate how skincolor perception of kayumanggi Filipina women is signified by her color choices in clothing. This research specifically aimed to define the specific skin color perception of kayumanggi Filipina, to identify her color choices and to understand how these choices reflect skincolor perception. Descriptive survey method with multi-method approach was used in this study. The researcher conducted interviews, wardrobe observations, attitude evaluation, and skincolor evaluations through the use of interview guide, ocular sheets, questionnaires and color charts. Ten kayumanggi Filipina were chosen to participate in the study. The subjects are currently residing in Metro Manila and studying in tertiary or post graduate school where uniform is optional or not required. Interviews were conducted during the personal visits of the researcher to the subjects' houses. Data gathered were organized through tabulations. Themes that emerged from the tabulation were counted, categorized and subjected to content analysis. Findings showed that there were two skincolor perceptions that were expressed by the subjects. First skincolor perception was the satisfaction with one's own complexion. This perception includes teh idea of individuality and the appreciation for one's skincolor. This was reflected by the subject's preference for green and white. Second skincolor perception was the dissatisfaction with one's skincolor. This includes fear of emphasizing dark skin, belief that cleanliness equals fairness, and regard for other people's opinion. This perception was shown by the subjects' aversion for neon colors, their preference for white and their conventional choice for black, purple and pink. The result of this research aims to challenge the readers to be critical on portraying their perceptions through their clothing. The study was also made for the purpose of inspiring more studies related to skincolor perception and other cultural factors that affect clothing choices.